2014
DOI: 10.1016/j.neuroimage.2014.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Handedness and effective connectivity of the motor system

Abstract: Handedness denotes the individual predisposition to consistently use the left or right hand for most types of skilled movements. A putative neurobiological mechanism for handedness consists in hemisphere-specific differences in network dynamics that govern unimanual movements. We, therefore, used functional magnetic resonance imaging and dynamic causal modeling to investigate effective connectivity between key motor areas during fist closures of the dominant or non-dominant hand performed by 18 right- and 18 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
101
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 64 publications
17
101
1
1
Order By: Relevance
“…This observation supports data that have revealed that interactions between hemispheres underline changes in processing demands due to handedness (Pool, Rehme, Fink, Eickhoff, & Grefkes, 2014;Reid & Serrien, 2012). Here, we noticed that right-handers showed suppression during movement as compared to rest, which suggests that inhibition of the contralateral hemisphere assists functional lateralisation.…”
Section: Functional Connectivity Patternssupporting
confidence: 92%
See 1 more Smart Citation
“…This observation supports data that have revealed that interactions between hemispheres underline changes in processing demands due to handedness (Pool, Rehme, Fink, Eickhoff, & Grefkes, 2014;Reid & Serrien, 2012). Here, we noticed that right-handers showed suppression during movement as compared to rest, which suggests that inhibition of the contralateral hemisphere assists functional lateralisation.…”
Section: Functional Connectivity Patternssupporting
confidence: 92%
“…Therefore, midline circuitry represents a relevant pathway that supports functional coupling patterns when righthanders perform movements with the non-dominant hand. This observation is in line with earlier fMRI research that has revealed that handedness guides effective connectivity within the motor network, including a significant role of the SMA (Pool et al, 2014). Taking into account that the coordination of brain systems was observed for complex rather than easy movements without a behavioural handedness effect, it suggests that these widespread interactions have limited 12 influence in supporting behavioural efficiency as compared to localised interactions between leftsided brain regions.…”
Section: Brain-behaviour and Brain System Correlationssupporting
confidence: 90%
“…Liu and colleagues found greater interhemispheric asymmetry in functional resting-state-connectivity of attention-related areas in right-handers compared to left-handers (Liu et al, 2009). We recently showed that effective connectivity, i.e., the causal influence that one area exerts over another area, between motor areas was differentially modulated in right-and left-handers depending on whether movements were performed with the dominant or non-dominant hand (Pool et al, 2014). More precisely, effective connectivity analysis revealed that in right-handed subjects movements of the dominant hand were associated with significantly stronger coupling of contralateral (left, i.e., dominant) supplementary motor area (SMA) with ipsilateral SMA, ipsilateral ventral premotor cortex (PMv), contralateral motor putamen and contralateral primary motor cortex (M1) (compared to equivalent connections in left-handers).…”
Section: Introductionmentioning
confidence: 90%
“…Thirty-six subjects [18 right-handers (10 males; 22-33 years old; mean age 26.1 ± 3.0 SD) and 18 left-handers (7 males; 19-30 years old; mean age 24.3 ± 2.6 SD)] with no history of neurological or psychiatric disease gave informed consent. Activation data of frequency-dependent modulation were previously published for this cohort of subjects (Pool et al, 2013(Pool et al, , 2014.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation